2011
DOI: 10.1002/ibd.21518
|View full text |Cite
|
Sign up to set email alerts
|

Ability of commonly used prediction equations to predict resting energy expenditure in children with inflammatory bowel disease

Abstract: Of the commonly used equations, the equation of Schofield should be used in pediatric patients with IBD when measured values are not able to be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Conversely, some situations (eg, critically ill patient with acute renal failure) may warrant moderate protein restriction. A comprehensive discussion of this issue is beyond the scope of this article but may be found elsewhere in the literature 30 , 34 38 …”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Conversely, some situations (eg, critically ill patient with acute renal failure) may warrant moderate protein restriction. A comprehensive discussion of this issue is beyond the scope of this article but may be found elsewhere in the literature 30 , 34 38 …”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Although a clinical study showed that n-3 PUFAs had no role in disease maintenance or remission [8], animal study even found that dietary fish oil exacerbates inflammatory colitis [9], Stenson et al [10] demonstrated that dietary supplementation with fish oil improved histological findings in UC patients. A study using enteric-coating fish oil preparations in UC patients showed that the relapse rate was markedly reduced, and laboratory inflammatory indicators were also reduced [11].…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports on the use of predictive equations for REE have highlighted the importance of population specificity . The original Japanese Dietary Reference Intakes (DRI) were formulated based on anthropometric measurements taken from 6500 Japanese subjects between 1951 and 1966 .…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al . reviewed population specificity for the choice of equation and reported that the Schofield equation (SE) is useful in pediatric patients with inflammatory bowel disease (IBD). Given that most of the existing predictive equations are based on Western populations, these equations may not be appropriate for Asian populations .…”
mentioning
confidence: 99%